IDENTIFICATION OF THE POTENTIALS AND CONSTRAINTS OF SELOKAN MATARAM UTILIZATION THROUGH A HERITAGE TOURISM APPROACH - Fatin Adilia (Kalyanamitra: Journal of Archaeological Resource Management, 2026)
This article examines the potentials and constraints of utilizing Selokan Mataram as a heritage tourism resource in Special Region of Yogyakarta. As a cultural heritage structure with historical, social, technological, cultural, and educational significance, Selokan Mataram demonstrates considerable potential for development as a heritage-based tourism destination. However, its primary function as an active irrigation system presents challenges for tourism utilization and management. This study aims to identify these potentials and constraints and to formulate preliminary management strategies that support both heritage conservation and tourism development. The research employs a qualitative descriptive-analytical method through a literature-based study by integrating values-based heritage management and the 4A tourism framework (attraction, amenity, accessibility, and ancillary services). The findings indicate that Selokan Mataram possesses strong tourism appeal as a living cultural landscape characterized by historical narratives and a functioning irrigation system. Nevertheless, its tourism readiness remains limited due to environmental degradation, infrastructure deterioration, inadequate facilities, and the absence of tourism-oriented institutional management. Therefore, the development of Selokan Mataram should be conducted gradually through environmental improvement, infrastructure enhancement, and institutional strengthening to maintain a balance between tourism utilization, heritage conservation, and its primary irrigation function.